Clinical update on the use of ospemifene in the treatment of severe symptomatic vulvar and vaginal atrophy - Palacios S; Cancelo MJ (Dove Medical Press, 2016)
Santiago Palacios,1 María Jesús Cancelo2 1Palacios Institute of Women’s Health, Madrid, Spain; 2Gynecology and Obstetrics Department, Guadalajara University Hospital, University of Alcalá, Spain Abstract: The physiological decrease in vaginal estrogens is accountable for the emergence of vulvar and vaginal atrophy (VVA) and its related symptoms such as vaginal dryness, dyspareunia, vaginal and/or vulvar irritation or itching, and dysuria. The repercussion of these symptoms on quality of life often makes it necessary to initiate treatment. Up until now, the treatments available included vaginal moisturizers and lubricants, local estrogens, and hormonal therapy. However, therapeutic options have now been increased with the approval of 60 mg ospemifene, the first nonhormonal oral treatment with an agonist effect on the vaginal epithelium and an endometrial and breast safety profile which makes it unique. This is the first selective estrogen receptor modulator indicated in women with moderate-to-severe vaginal atrophy not eligible for local estrogen treatment. Considering that “local estrogen noneligible women” are those in whom such treatment cannot be administered either because it is contraindicated or due to skill issues, who are averse to the mode and convenience of vaginal products’ administration or to their use on account of potential systemic absorption, or those who demonstrate dissatisfaction in terms of efficacy and safety, it is clear that there is a significant unmet medical need in VVA management. In fact, a great number of women show lack of adherence, dropping out of at least one VVA treatment, including nonhormonal moisturizers and lubricants, which they consider to be ineffective and uncomfortable. If they could choose, many of them may opt for oral treatment. In Phase III studies, ospemifene demonstrated efficacy in vaginal dryness and dyspareunia, regenerating vaginal cells, improving lubrication, and reducing pain during sexual intercourse. Symptoms improved in the first 4 weeks and endured for up to 1 year. Additionally, it demonstrated a good endometrial, cardiovascular system, and breast safety profile. Keywords: ospemifene, vulvar and vaginal atrophy, dyspareunia, therapeutic options